Development of a transfer model for the design and the operation of sodium purification systems for fast breeder reactors. (February 2015) - Khatcheressian, Nayiri; Latgé, Christian; Joulia, Xavier; Gilardi, Thierry; Meyer, Xuan
<x xml:space="preserve">Abstract</x> Operating a Sodium Fast Reactor (SFR) in reliable and safe conditions requires mastering the quality of the sodium fluid coolant, regarding oxygen and hydrogen impurities contents. A cold trap is a purification unit in SFR, designed to maintain oxygen and hydrogen contents within acceptable limits. The purification of these impurities is based on crystallization of sodium hydride on cold walls and sodium oxide or hydride on wire mesh packing. Indeed, as oxygen and hydrogen solubilities are nearly nil at temperatures close to the sodium melting point, i.e., 97.8 °C, on line sodium purification can be performed by cooling down liquid sodium flows and promoting crystallization of sodium oxide and hydride. However, the management of cold trap performances is necessary to prevent from unforeseen maintenance operations, which could induce shut‐down of the reactor. It is thus essential to understand how a cold trap fills up with impurities crystallization in order to optimize the design of this system and to overcome any problems during nominal operation. This paper deals with the mathematical modelling of crystallization process in a cold trap and predicts the location and the amount of the impurities deposit, on cold walls for sodium hydride and on wire mesh packing for sodium oxide. A model of the front propagation by "diffuse deposit interface method" was developed and sensitivity to various parameters was evaluated. These results will enable to understand the consequences of the impurities deposited on the hydrodynamics and heat transfer in a cold trap.